Discourse Analysis on Language Policy in Presidential Regulation (Perpres) No. 63 of 2019 concerning the use of Indonesian (Indonesia Language) - supri, supriadi; Marpaung, Fernando De Napoli; Dewi, Resti Citra (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2023)
Presidential Regulation (Perpres) Number 63 of 2019 concerning the use of the Indonesian language is an Indonesian government policy issued on 30 September 2019. This study aims to analyze and understand the implementation of language policy in Presidential Regulation (Perpres) No. 63 of 2019 concerning the Use of Indonesian in Indonesia. The research method used is a qualitative method with a critical discourse analysis approach. The result and discussion of articles 23, 24, and 31 of Presidential Regulation (Perpres) No 63 of 2019 concerning the use of Indonesian, the Indonesian national education system shows the importance of language in education and knowledge production. The discourse analysis using Van Dijk's theory highlights the influence of government policies, attention to cultural and linguistic diversity, and technological developments in shaping language use in education and scientific work in Indonesia. Regulations and policies related to the use of Indonesian, regional languages, and foreign languages in education demonstrate the complex relationship between language, text, context, and knowledge in building an understanding of education policy in Indonesia. The implications of this research can be used as a reference for policy makers and decision makers in formulating more effective and sustainable language policies in Indonesia.